First year experiences with a palliative out-patients structure for patients with COPD: a qualitative study of health professionals’ expectations and experiences - Dorthe Gaby Bove; Marie Lavesen; Maria Omel Jellington; Kristoffer Bastrup-Madsen Marsaa; Suzanne Forsyth Herling (BMC Palliative Care, 2018)
Abstract Background To improve the care of patients with advanced COPD and be able to address their palliative needs a new outpatient organization (CAPTAIN) was developed and implemented. CAPTAIN was inspired by best practice and existing guidelines and changed the traditional organization of an outpatient structure including the roles of nurses and doctors. Only sparse knowledge exists of the health professionals’ expectations and experiences to organizational changes in an outpatient setting. This insight is necessary as health professionals are key stakeholders in implementing new structures and successfully transforming knowledge into practice. The aim of this study was to explore the health professionals’ expectations and experiences of a new palliative out-patients structure for patients with advanced COPD. Methods The design was interpretive description as described by Thorne. Focus groups and individual interviews were conducted with pulmonary nurses, pulmonary doctors and municipality nurses from 2014 to 2016. Results The overall theme was dualism. Both nurses and doctors were pending between aspiration and concern in their expectations to the new structure, meanwhile their actual experiences were pending between perceived gain and improvements versus consequences with the new structure. Nurses’ and doctors’ existing practice was altered and the new structure required new ways for them to cooperate and ways in which skills from each profession were most efficiently utilized. Conclusion Nurses and doctors considered the new structure as a quality boost and it fulfilled their hope of improving the quality of care offered to patients with advanced COPD, however with increased work-related stress as a derived consequence.